Temperature‐Responsive Luminescent Solar Concentrators: Tuning Energy Transfer in a Liquid Crystalline Matrix - Sol, Jeroen A. H. P. (Angew Chem Int Ed Engl, 2017)
Temperature‐responsive luminescent solar concentrators (LSCs) have been fabricated in which the Förster resonance energy transfer (FRET) between a donor–acceptor pair in a liquid crystalline solvent can be tuned. At room temperatures, the perylene bisimide (PBI) acceptor is aggregated and FRET is inactive; while after heating to a temperature above the isotropic phase of the liquid crystal solvent, the acceptor PBI completely dissolves and FRET is activated. This unusual temperature control over FRET was used to design a color‐tunable LSC. The device has been shown to be highly stable towards consecutive heating and cooling cycles, making it an appealing device for harvesting otherwise unused solar energy.